Intelligent data acquisition and cloud services for apple orchard - Xiang, Guo; Lihua, Zheng; Minzan, Li; Yao, Zhang (International Journal of Agricultural and Biological Engineering, 2014)
An intelligent data acquisition and service system for orchard was developed for acquiring apple tree growth information in time and managing orchard production remotely. The data of fruit tree growth environment were collected by PDA (Portable Digital Assistant) through the ZigBee WSN (wireless sensors network) deployed in the apple orchard. The collected data were packaged and uploaded following the transportation protocol through the web service interface provided by the orchard server. After that the orchard data were parsed and stored using distributed mechanism. Finally, the data could be processed, analyzed and visualized by the cloud orchard server, and the orchard production decisions based on WebGIS technology could be made as well. Hence the users could access the services provided by the network platform via remote movable or fixed terminals. The system test run showed that the whole process was stable and reliable, during which intelligent data collection, storage, and cloud data processing and services were achieved. Keywords: orchard, PDA, WSN, WebGIS, distributed storage, web service DOI: 10.3965/j.ijabe.20140702.018 Citation: Guo X, Zheng L H, Li M Z, Zhang Y. Intelligent data acquisition and cloud services for apple orchard. Int J Agric & Biol Eng, 2014; 7(2): 146－153.